Doctor’s responsibility and end of life: the right to negotiate "time" - Ciliberti, Rosagemma; Ciaccia, Romina; Alfano, Linda (Medicina Historica, 2022)
The end of life continues to be at the center of a lively debate that involves complex and heterogeneous ethical issues (palliative care, pain therapy, the freedom to refuse treatment, therapeutic obstinacy, advance treatment provisions) and that, today, are polarized on access to the request to end one’s existence affected by an illness with a poor prognosis and source of suffering. An aspect of great importance, still little explored on the ethical level, concerns the right of persons suffering from intreatable pathologies to live their time in accordance with their own demands. The work aims to investigate the person’s right to self-determination and to plan in the way deemed most appropriatethe last years or months of his life, as a distinct and autonomous right with respect to that pertaining to the loss of chances of healing. This instance recognizes the patient’s active and aware capacity to organize materially and spiritually his remaining time within his own personal option of value. The authors comment on a ruling by the Supreme Court of Cassation that has emphasized that the system must not be at all indifferent to the need of the human being "to enter death with open eyes".